DISPARITAS PEMIDANAAN TERHADAP PELAKU PEMBUNUHAN BERENCANA DENGAN MUTILASI (STUDI KASUS PUTUSAN NOMOR 1036/Pid.B/2008/PN.DPK dan 44/Pid.B/2014/PN.SRP) - Hana Juniana; Nurfaidah; Uum (Gayaku Publisher, 2024)
Murder by mutilation is a very cruel act, where the act begins with taking a person's life and continues with cutting the victim's body from the head to the entire body. This action was carried out with the aim of eliminating evidence or traces of the murder. Mutilation is also not strictly regulated in Indonesian criminal law, so that when imposing sanctions on the perpetrator there is often uncertainty and inconsistency. This causes concern and discomfort in society, especially if the perpetrator does not receive appropriate punishment. Therefore, this research aims to find out how the judge considered in making decisions in these two cases based on the positive legal system in Indonesia and to find out what caused the disparity in the two decisions. The research method used is normative legal research which examines and examines primary, secondary and tertiary legal materials in the form of statutory regulations and library law